Molecular analysis of Sarcoptes scabiei infecting wild and domestic South American camelids in Argentina - Anello, Melina (2025)
Sarcoptic mange, caused by the Sarcoptes scabiei mite, is a highly transmissible skin condition affecting many mammalian species worldwide. South American camelids (SAC) have the highest reported prevalence of mange in South America, causing economic losses and posing a conservation threat to wild SAC. This study investigated mite diversity in SAC in Argentina and assessed relationships between known outbreak areas. Distinct epidemiologic scenarios were explored: the San Juan-La Rioja region, where a mange outbreak decimated wild SAC populations, and the Puna region of Jujuy, where domestic and wild SAC coexist and infections often occur. The mitochondrial gene cox1 and ten microsatellites were analysed from mites collected in five sampling events in Jujuy and four in San Juan-La Rioja between 2017 and 2023. A single cox1 haplotype was observed regardless of mite origin or host species. Comparison with partial cox1 sequences from other camelids worldwide showed little variation. Microsatellite markers revealed lower diversity in mites from San Juan-La Rioja compared to Jujuy. A single strain common to vicuñas and guanacos was identified in San Juan-La Rioja, while three strains were detected in Jujuy affecting vicuñas and/or domestic llamas. Some mites from Jujuy exhibited mixed genetic composition between the two regions, and results confirmed that domestic and wild SAC shared mite strains. This study enhances understanding of sarcoptic mange transmission among SAC species, contributing to vicuña and guanaco conservation and high-altitude livestock farming. Additionally, these findings provide support for the development of intersectoral management strategies to address this significant threat.